Simulation Research of the Solid Filling Hydraulic Support Hangs Scraper Conveyor - Zhang Dongsheng; Yuan Shuai; Yuan Zhi; Song Qiushuang; Gao Hao (Jixie chuandong)
By establishing the mechanical model,the analysis study on scraper chain tension variation is carried out,through the MATLAB software,the change rule of scraper chain tension under different working condition is simulated. Through finite element analysis software ANSYS Workbench,the finite element analysis of central trough of scraper chain sunroof open and close two states under load conditions is carried out,the stress concentration and the maximum displacement positions of the condition are determined,it is found that the strength of hanging ear plate is not enough,after the material replacement for Q690,the strength requirement is meet. According to the result of finite element analysis and statics analysis and calculation,by using n Code software,the fatigue strength analysis is carried out on the scraper chain,the life and injury cloud chart are obtained,it in line with the finite element analysis results and can satisfy the requirements of use.